2019
DOI: 10.1111/lam.13199
|View full text |Cite
|
Sign up to set email alerts
|

Growth and fatty acid profiles ofHalophytophthoravesiculaandSalispinaspinosafrom Philippine mangrove leaves

Abstract: Studies on marine‐sourced fatty acids have gathered significant interest recently as an important component of aquaculture feeds and of biofuel production. Of the organisms capable of producing fatty acids, marine oomycetes are promising model organisms. One group of marine oomycetes are the Halophytophthora spp. which is known to have an important role in leaf decomposition, thereby changing the plant debris into exudates which are usable to consumers in the mangrove ecosystems. This study reports the three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Members of Salispina are reported as estuarine species, whereas Rhipidiaceae thrive in freshwater biomes (Dick 2001). In the Philippines, Salispina hoi, S. lobata, and S. spinosa have been isolated from mangrove leaf litter (Leaño 2001, Bennett et al 2018, Caguimbal et al 2019.…”
Section: Overview Of the Estuarine Oomycetes Phylogenymentioning
confidence: 99%
See 2 more Smart Citations
“…Members of Salispina are reported as estuarine species, whereas Rhipidiaceae thrive in freshwater biomes (Dick 2001). In the Philippines, Salispina hoi, S. lobata, and S. spinosa have been isolated from mangrove leaf litter (Leaño 2001, Bennett et al 2018, Caguimbal et al 2019.…”
Section: Overview Of the Estuarine Oomycetes Phylogenymentioning
confidence: 99%
“…elongata, and S. bahamensis. Recently, several studies explored the fatty acid composition of Philippine mangrove oomycetes, and some isolates produced good amounts of polyunsaturated fatty acids (Say et al 2017, Caguimbal et al 2019. Despite these taxonomic proposals and applied studies, oomycete research in the Philippines, particularly reagarding the saprotrophic and marine groups, is still underexplored.…”
Section: Oomycetes In the Philippinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several aquatic microorganisms have also been explored, with microalgae and thraustochytrids giving promising results in terms of the production of PUFAs, in particular omega-3 FAs [26][27][28]. Oomycetes have mostly been overlooked, although several studies showed that members from several genera, including Halophytophthora, Phytophthora, Pythium and Salispina, can produce a wide variety of FAs [29][30][31][32][33]. Pang et al [31] reported, for the first time, the production of arachidonic acid (ω-6, ARA) and eicosapentaenoic acid (ω-3, EPA) by different Halophytophthora species isolated from fallen mangrove leaves in Taiwan, suggesting these oomycetes as a potential alternative source of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2015; Caguimbal et al . 2019). One of these factors is the monitoring and cell growing control; which despite the efforts made, still presents opportunity areas, mainly regarding adequate measuring, wavelengths selection and the establishment of specific standard curves for each microalgae species and/or specific culture conditions (Lee et al .…”
Section: Introductionmentioning
confidence: 99%